The fibers of the circular junction of the linea alba in normal adult anatomy. Issue 6 (19th January 2021) - Merh, Radhika; Saunders, Michael; Jenner, Deborah
Abstract: The linea alba (LA) is known to be useful to surgeons for making surgical incisions. Laparoscopic entry into the peritoneal cavity using the open technique may involve identification of a point just above or below the umbilicus where the peritoneum is fused to the LA. This anatomical site is found through superficial dissection to expose the junction between the umbilical stalk (US) and the LA, where distinct fibers seem to form a unique ligament‐like structure in normal adult anatomy. This point, in fact, is part of a circular fibrous structure that exists almost like a ring around the remnant US. It is formed by the fusion of oblique and transverse fibers of the LA with circular fibers from proliferation of an encircling band of compact mesoderm to close a patent umbilical ring. We describe and name this anatomical landmark as junctio circularis alba or the "circular junction of the LA" as encountered in normal adult human anatomy. We believe this is crucial for describing key surgical procedures at this site to aid effective surgical training and reduce iatrogenic complications from laparoscopic port site entries.